2019
DOI: 10.1002/er.4595
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling of microfluidic fuel cell using planar single stacks

Abstract: Summary The commercialization of microfluidic fuel cells remains difficult because of their low‐power density. In this study, microfluidic fuel cells with a planar single‐stack structure are proposed to improve the power density. The proposed stacks connect multiple cells in series, parallel, series–parallel, and parallel–series configurations. The electrolyte flow patterns of the stacks were numerically analyzed, and cell performances were experimentally measured with a platinum electrode using formic acid as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…(Reprinted with permission (through Copyright Clearance Central) from reference (Moreno‐Zuria et al, 2014) Copyright © 2014, Elsevier); (f) A schematic illustration representing a microfluidic cell with cylindrical array anodes to tackle the perturbance generated at the co‐laminar interface due to product CO 2 generation. (Reprinted with permission (through Copyright Clearance Central) from reference (Zhu et al, 2014) Copyright © 2013, Elsevier); (g) Various combinations of planar single stacks in (A) four‐series, (B) four‐parallel, (C) two‐series and then two‐parallel, and (D) two‐parallel and then two‐series (Reprinted with permission (through Copyright Clearance Central) from reference (S. H. Lee & Ahn, 2019) Copyright © 2019, John Wiley & Sons, Ltd.); (h) Comparison of a paper based microfluidic fuel cell and a commercial lateral flow test strip for dengue diagnosis. (Reprinted with permission (through Copyright Clearance Central) from reference (Esquivel et al, 2014) Copyright © 2014, The Royal Society of Chemistry); (i) Schematic illustration of single‐inlet paper‐pencil fuel cell.…”
Section: Dfafc Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Reprinted with permission (through Copyright Clearance Central) from reference (Moreno‐Zuria et al, 2014) Copyright © 2014, Elsevier); (f) A schematic illustration representing a microfluidic cell with cylindrical array anodes to tackle the perturbance generated at the co‐laminar interface due to product CO 2 generation. (Reprinted with permission (through Copyright Clearance Central) from reference (Zhu et al, 2014) Copyright © 2013, Elsevier); (g) Various combinations of planar single stacks in (A) four‐series, (B) four‐parallel, (C) two‐series and then two‐parallel, and (D) two‐parallel and then two‐series (Reprinted with permission (through Copyright Clearance Central) from reference (S. H. Lee & Ahn, 2019) Copyright © 2019, John Wiley & Sons, Ltd.); (h) Comparison of a paper based microfluidic fuel cell and a commercial lateral flow test strip for dengue diagnosis. (Reprinted with permission (through Copyright Clearance Central) from reference (Esquivel et al, 2014) Copyright © 2014, The Royal Society of Chemistry); (i) Schematic illustration of single‐inlet paper‐pencil fuel cell.…”
Section: Dfafc Designsmentioning
confidence: 99%
“…For a cell using FA as the fuel and potassium permanganate as the oxidant, the peak power and scaling‐up efficiency of the mixed connections were better than series or parallel connections. The size of the stack was further reduced by designing a common‐feed inlet stream to unify the fuel inlets and oxidant inlets as two single inlet streams (S. H. Lee & Ahn, 2019).…”
Section: Dfafc Designsmentioning
confidence: 99%
“…[15][16][17] By now, extensive studies have been reported to boost the MFC output with various methods, including the introduction of innovative channel geometries, 10,18,19 the design of novel electrode configurations, 20,21 the development of robust catalysts, 22 the use of different redox chemistry, 9,23,24 the application of hydrodynamic focusing technology 25 and the implementation of the stack strategy. 5,26,27 Among them, MFC with porous electrodes in a flow-through configuration is outstanding owing to its remarkably high power density. 28 Compared with the flow-over type MFC where the catalysts are deposited on a two-dimensional (2D) support, the flowthrough type MFC using porous electrodes can bring enhanced mass transport due to the high specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to advantages of simple structure, low cost, and eliminating membrane-related issues, MMFCs have received much attention and been considered as a promising miniature power source for portable devices. [1][2][3] Over the past decade, the performance of the MMFC has been improved from tens of μW cm −2 to hundreds of mW cm −2 by changing reactants, 4-7 modifying electrode structure, [8][9][10][11][12] or optimizing fuel cell design. [13][14][15][16][17] However, syringe pumps are needed to keep fuel and oxidant flow laminarly in parallel in most of microfluidic fuel cells, thus increasing the overall size of the system and limiting their miniaturization.…”
Section: Introductionmentioning
confidence: 99%
“…Two streams mix together only by the transverse diffusion. Owing to advantages of simple structure, low cost, and eliminating membrane‐related issues, MMFCs have received much attention and been considered as a promising miniature power source for portable devices . Over the past decade, the performance of the MMFC has been improved from tens of μW cm −2 to hundreds of mW cm −2 by changing reactants, modifying electrode structure, or optimizing fuel cell design .…”
Section: Introductionmentioning
confidence: 99%